In vitro modulatory effects of ginsenoside compound K, 20(S)-protopanaxadiol and 20(S)-protopanaxatriol on uridine 5′-diphospho-glucuronosyltransferase activity and expression - Jang, Su-Nyeong; Park, So-Young; Lee, Hyunyoung; Jeong, Hyojin; Jeon, Ji-Hyeon; Song, Im-Sook; Kwon, Mi Jeong; Liu, Kwang-Hyeon (Xenobiotica, 2021)
We explored the inhibitory effect of ginsenoside compound K (CK), 20(S)-protopanaxadiol (PPD), and 20(S)-protopanaxatriol (PPT) on six uridine 5′-diphospho-glucuronosyltransferase (UGT) enzyme (UGT1A1, 1A3, 1A4, 1A6, 1A9, and 2B7) activities in human liver microsomes (HLMs) and 10 UGT enzyme (UGT1A1, 1A3, 1A4, 1A6, 1A9, 2B4, 2B7, 2B10, 2B15, and 2B17) activities in recombinant UGT isoforms. PPD was a potent inhibitor of UGT1A3 activity with half-maximal inhibitory concentration values of 5.62 and 3.38 μM in HLMs and recombinant UGT1A3, respectively. UGT1A3 inhibition by CK and PPD was competitive with inhibitory constant (K i ) values of 17.4 and 1.21 μM, respectively, and inhibition by PPT was non-competitive with a K i value of 8.07 μM in HLMs. PPD exhibited more than 3.4-fold selectivity for UGT1A3 inhibition compared with other UGT isoforms inhibition, while CK and PPT showed more than 2.16- and 2.21-fold selectivity, respectively. PPD did not significantly increase the mRNA expression of UGT1A1, 1A3, 1A4, 1A9, and 2B7 in hepatocytes. Given the low plasma concentrations of PPD in healthy human subjects and the absence of induction potential on UGT isoforms, we conclude that PPD cause no pharmacokinetic interactions with other co-administered drugs metabolised by UGT1A3.